Youth sport dropout according to the process-person-context-time model: a systematic review - Kylie Moulds, Sheila Galloway, Shaun Abbott, Stephen P. Cobley (International Review of Sport and Exercise Psychology, 2024)
Examined from Bio-Ecological System Theory`s PPCT model perspective, this study systematically reviewed how youth sport dropout literature has been theoretically framed; how dropout has been defined and measured; and, mapped all influential factors previously associated (or not) with dropout across and within youth sport. Peer-reviewed literature (N = 69 studies) published over four decades (1980-2021) residing within five databases was synthesised using a mixed-methods review approach. Existing identified studies examined single or multi-sport (male and female) youth sport contexts worldwide, at different participation levels, although predominantly local club-level. Prior studies predominantly adopted psychological-based theoretical frameworks; often didn`t define dropout; assessed dropout descriptively; and, focused upon the influence of psychological-based factors. From a PPCT perspective, competition structure, relative age (Process), sex, competence perception (Personal), parental socio-demographics, and conflicts with other activities (Context) were frequently identified as influential to dropout across contexts. Although not explicitly utilising the PPCT, sixteen studies examined factors across PPCT levels, with one identifying significant independent influences across the model. Future research is recommended to apply more encompassing (social-ecological) theoretical frameworks; specify dropout definitions and measures; and apply more advanced analytical methods. To help improve study methodological quality, the `Youth Sport Dropout - Study Checklist (YSD-SC)` is presented.